Benefits of simultaneous laparoscopic resection of primary colorectal cancer and liver metastases. Issue 1 (15th October 2013) - Takasu, Chie; Shimada, Mitsuo; Sato, Hirohiko; Miyatani, Tomohiko; Imura, Satoru; Morine, Yuji; Ikemoto, Tetsuya; Kanamoto, Mami; Kurita, Nobuhiro; Eto, Shohei; Utsunomiya, Tohru
Abstract Introduction Recently, consensus on the optimal strategy for resectable synchronous colorectal liver metastases (LM) seems to have shifted toward simultaneous resection. However, there are still relatively few reports about simultaneous laparoscopic resection. The aim of this study is to evaluate the outcomes of patients who underwent simultaneous laparoscopic resection. Methods We evaluated 14 patients who underwent simultaneous resection of primary colorectal cancer and LM in our hospital from 2004 to 2012. Patients were selected by matched pair analysis based on the number of LM (≤4) and tumor size (≤5 cm). We divided them into two groups: the simultaneous laparoscopic resection of primary colorectal cancer and LM (Lap‐S) group (n = 7) and the simultaneous open resection of primary colorectal cancer and LM (Open‐S) group (n = 7). Clinical and oncologic outcomes were compared between the groups. Results The Lap‐S patients were significantly older than the Open‐S patients. The mean operative times of Lap‐S and Open‐S were 472 min and 466 min, respectively. The mean blood loss was significantly smaller in the Lap‐S group (153 mL) than in the Open‐S group (496 mL). There was no surgical mortality in either group. The incidence of postoperative complications in the Lap‐S and Open‐S groups was 12.3% and 33.0%, respectively. The mean postoperative hospital stay was significantly shorter in the Lap‐S group (16 days) than in the Open‐S group (36 days). There was no significant difference in long‐term survival between the two groups. Conclusion Lap‐S patients had equivalent long‐term outcomes to Open‐S patients. Therefore, given its technical feasibility and safety, Lap‐S may be one of the most promising options in selected patients.